2013
DOI: 10.1016/j.metabol.2013.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Branched chain and aromatic amino acids change acutely following two medical therapies for type 2 diabetes mellitus

Abstract: Objective Elevated circulating levels of branched chain and aromatic amino acids (BCAA/AAAs) are associated with insulin resistance and incident type 2 diabetes (T2D). BCAA/AAAs decrease acutely during an oral glucose tolerance test (OGTT), a diagnostic test for T2D. It is unknown whether changes in BCAA/AAAs also signal an early response to commonly used medical therapies for T2D. Materials and Methods A liquid chromatography-mass spectrometry approach was used to measure BCAA/AAAs in 30 insulin sensitive (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 15 publications
6
56
0
Order By: Relevance
“…For each diet, we examined the direction of change in the concentrations of the metabolites that have been shown to predict the risk of type 2 diabetes (31,32,(38)(39)(40)(41)(42). We annotated each metabolite by whether the change by diet was in the direction that increased or decreased risk of disease.…”
Section: Disease Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…For each diet, we examined the direction of change in the concentrations of the metabolites that have been shown to predict the risk of type 2 diabetes (31,32,(38)(39)(40)(41)(42). We annotated each metabolite by whether the change by diet was in the direction that increased or decreased risk of disease.…”
Section: Disease Riskmentioning
confidence: 99%
“…Multiple metabolites that have been linked to risk of type 2 diabetes (31,32,(38)(39)(40)(41)(42) showed strong or moderate associations with diet, including amino acids (isoleucine, leucine, valine, tyrosine, serine and glutamine), lipids (C18:2 lysophosphatidylethanolamine (LPE), C22:6 LPE, C56:9 TAG, C58:10 TAG, and C60:12 TAG), and others (2-aminoadipate, betaine, and C3 carnitine) as depicted in Supplemental Figures 5 and 6. The concordance between the metabolite profile that predicts type 2 diabetes risk and the dietassociated changes varied across classes of metabolites.…”
Section: Effect Of Diet On Metabolites That Predict Disease Riskmentioning
confidence: 99%
“…Clinical intervention studies have also reported that decreased BCAA concentrations following an intervention (e.g. gastric bypass surgery or medical therapy) correlated with improvements in glucose homeostasis [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Walford et al [14] involved administering either metformin, glipizide or glucose challenge to type 2 diabetes patients. In patients who were insulin sensitive, branched chain amino acids and aromatic amino acids decreased in response to release of insulin, as happened when they were given either glipizide or glucose challenge.…”
Section: Anti-diabeticsmentioning
confidence: 99%